Écart et séduction : Gérard de Nerval et Derek Mahon - Maryvonne Boisseau (Sillages Critiques)
A translator is inevitably confronted with the irreducible difference between languages which is often perceived in a negative way. However, the experience of difference itself is necessary for translation to happen. The process of translation will then aim at constructing the difference positively through various means that range from resorting to expedient language resources to adapting the text. It will be argued that a process of seduction consisting in finding ways to come to terms with the original text is at work behind all this. Thus this paper is an attempt at theorizing the idea of difference with regard to a process of seduction of the text that aims at appropriating and controlling the difference between the two languages. Consequences on the experience of translation and position of the translator will be considered and illustrated by a contrastive reading of De Nerval’s “Vers dorés” and Mahon’s versions of the poem.